Spatial and temporal patterns of methane emissions from mountain peatlands in the northern Andes across a disturbance gradient - Benavides, J. C.; Rocha, Santiago; Blanco, E. A. (Frontiers in Earth Science, 2023)
Methane emitted by wetlands accounts for nearly 30% of the global methane emissions and is expected to double by 2100. Methane fluxes from peatlands are related to m soil temperature, water table, and vegetation. Disturbances, mostly drainage, are considered to have a more limited impact on CH4 fluxes from peatlands. Here, we studied the temporal and spatial patterns of methane emissions from four peatlands across and elevation and disturbance gradient in the northern Andes. Our research seeks to understand the effects of disturbance legacies and soil temperature, flooding patterns, and vegetation on methane emissions in Andean peatlands. Our results indicated a strong control of CH4 emissions by soil temperature with a stronger effect at intermediate elevations. The removal of peat forming vegetation from the surface had the higher effect on CH4 emissions, increasing methane fluxes by an order of magnitude. Methane fluxes from conserved cushion vascular plants were low, but nearby hollows had relatively high emissions. Our research provides evidence of high methane emissions from degraded peatlands in the tropical Andes. However, the role of climate change and disturbance legacies on methane emissions from tropical Andean peatlands remains unknown affecting our ability to predict future emission patterns and our ability to incorporate climate mitigation strategies.